Programming 32-Bit Microcontrollers in C - Exploring the PIC32 - Di Jasio, Lucio (Embedded technology series, 2008)
The new 32-bit microcontrollers bring the promise of more speed and more performance while offering an unprecedented level of compatibility with existing 8 and 16-bit PIC microcontrollers. In sixteen engaging chapters the author puts all these claims to test while offering a gradual introduction to the development and debugging of embedded control applications in C. The author, a PIC and embedded control expert, offers unique insight into the new 32-bit architecture while developing a number of projects of growing complexity. Embedded programmers, designers and newcomers to the field alike will benefit from the text’s many thorough examples which demonstrate how to nimbly side-step common obstacles, solve real-world design problems efficiently and optimize code using the new PIC32 features and peripheral set. Each chapter of the book is offered as a day of exploration in the 32-bit embedded programming world.